2006
DOI: 10.1080/09515070600960498
|View full text |Cite
|
Sign up to set email alerts
|

Living the scientist-practitioner model in a psychology training clinic

Abstract: Counselling psychology has long espoused the scientist-practitioner model. An early career counselling psychologist working in a doctoral program as both a faculty member and training clinic director describes his current work setting, his relatively recent scientist-practitioner training, and the ways in which embracing this model promotes a sense of professional identity. He also presents the psychology training clinic as a model professional home for counselling psychologists and scientist-practitioners. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Departmental training clinics and university counseling centers continue to provide counseling psychology students integrative training experiences. Because routine outcome assessment is now the norm in departmental training clinics, some have suggested that departmental training clinics offer an ideal setting for the integration of science and practice (e.g., Sauer, 2006; Sauer & Huber, 2007). In these settings, outcome data are used to track clinical outcomes, inform clinical decision-making, and conduct naturalistic research.…”
Section: Characteristics Of a Model Counseling Psychology Doctoral Prmentioning
confidence: 99%
“…Departmental training clinics and university counseling centers continue to provide counseling psychology students integrative training experiences. Because routine outcome assessment is now the norm in departmental training clinics, some have suggested that departmental training clinics offer an ideal setting for the integration of science and practice (e.g., Sauer, 2006; Sauer & Huber, 2007). In these settings, outcome data are used to track clinical outcomes, inform clinical decision-making, and conduct naturalistic research.…”
Section: Characteristics Of a Model Counseling Psychology Doctoral Prmentioning
confidence: 99%
“…By providing clinical services through a university training clinic, the instructor can avoid the time‐consuming responsibilities of scheduling and billing (Ray et al., ). Teaching loads could be reduced to support faculty involvement in the campus training clinic (Sauer, ). If practice hours were mandatory, then the university would be forced to make accommodations for practice, the department could expand the use of the training clinic and the billing office could provide faculty members with a portion of the fees earned.…”
Section: Discussionmentioning
confidence: 99%
“…By providing clinical services through a university training clinic, the instructor can avoid the time-consuming responsibilities of scheduling and billing (Ray et al, 2014). Teaching loads could be reduced to support faculty involvement in the campus training clinic (Sauer, 2006).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…The literature shows that the scholar-practitioner is called by many names: "practitioner-theorist" (Lynham, 2002, p. 224); "scholarly practitioners" (Ruona, 1999, p. 895); "boundary-spanner" and "semiotic broker" (Tenkasi & Hay, 2004, p. 179); "ambassador," "partner," and "champion" (Short, 2006b); and "scientist-practitioner" (Barraclough, 2006;Sauer, 2006;Stone, 2006). Given these many titles, we begin with exploring "scholar" and "practitioner."…”
Section: The Scholar-practitionermentioning
confidence: 99%